2020
DOI: 10.3390/cells9051238
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Neurofilament Light Splicing and Misbalance in Zebrafish

Abstract: Neurofilaments (NFs), a major cytoskeletal component of motor neurons, play a key role in the differentiation, establishment and maintenance of their morphology and mechanical strength. The de novo assembly of these neuronal intermediate filaments requires the presence of the neurofilament light subunit (NEFL), whose expression is reduced in motor neurons in amyotrophic lateral sclerosis (ALS). This study used zebrafish as a model to characterize the NEFL homologue neflb, which encodes two different isoforms v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, TDP-43 binds with NEFL mRNA at its 3'UTR (MJ, 2007 ). A recent study in zebrafish revealed that MO-mediated knockdown of TDP-43 disrupts the splicing of NEFL zebrafish ortholog neflb , as the overexpression of one isoform of neflb rescued the reduction in the motor neuron axon length of TDP-43 knockdown embryos, while the other isoform exacerbated the phenotypes (Demy et al, 2020 ).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Interestingly, TDP-43 binds with NEFL mRNA at its 3'UTR (MJ, 2007 ). A recent study in zebrafish revealed that MO-mediated knockdown of TDP-43 disrupts the splicing of NEFL zebrafish ortholog neflb , as the overexpression of one isoform of neflb rescued the reduction in the motor neuron axon length of TDP-43 knockdown embryos, while the other isoform exacerbated the phenotypes (Demy et al, 2020 ).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Two isoforms of the latter gene, neflE3 and neflE4, are generated by alternative splicing of neflb mRNA ( Fig. 1B ) ( Demy et al, 2020 ). Alternative use of two polyadenylation sites in exon 4 in the mouse NfL gene also generates 2.3-and 3.5-kb mRNAs ( Nakahira et al, 1990 ).…”
Section: Posttranscriptional Regulation Of Nflmentioning
confidence: 99%
“…The functional significance of this observation is not yet understood. Recent studies showed that disruption of the balance of the two isoforms of NfL mRNAs through partial deletion of TDP43 affects Nf assembly and motor axon growth with resultant motor deficits in zebrafish ( Demy et al, 2020 ). More recent studies demonstrated that TDP43 proteinopathy can cause translational suppression of Nf mRNAs resulting in 3-4-fold decrease in the levels of NfPs in mouse brain ( Kumar et al, 2021 ).…”
Section: Posttranscriptional Regulation Of Nflmentioning
confidence: 99%
“…Moreover, depleting both tardbp and tardbpl simultaneously caused a harsher zebrafish phenotype, comprising weight loss, reduced survival and muscle atrophy on top of the swimming and motor deficits, which were already present upon a tardbp-only KO [188,190,191]. Recently, zebrafish experiments showed that neurofilament splicing, essential for proper axonal transport and overall motor neuron health, was regulated by TDP-43, suggesting that both factors might be biologically and pathologically associated [192]. Further substantiation of zebrafish transgenic lines as assets for the investigation of TDP-43 ALS was found by performing comparative sequencing analyses.…”
Section: Tardbpmentioning
confidence: 99%